Penghambat Kepatuhan Terapi Antiretroviral Pada Orang Dengan HIV/AIDS (Studi Kasus Pada ODHA Loss To Follow Up Therapy) - Mukarromah, Sholihatul; Azinar, Muhammad (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2021)
Background: In 2019, the new case of HIV in Jepara was 138 cases which caused Jepara was on high ranked in Central Java. This is caused by the bad behavior of PLWHA, especially PLWHA who doesn’t obey their ARV Therapy, causing transmission of HIV disease to others. This study aims to determine the barriers to adherence to ARV Therapy in PLWHA in Jepara. Methods: The research used a qualitative method with a case study method. Data collection by in-depth interviews, observation, and documentation of 8 HIV/AIDS patients loss to follow-up antiretroviral therapy. Data analysis was done descriptively with the triangulation method. Results: The results of the analysis showed that lack of knowledge, poor perception of vulnerability, side effects of drugs, depression and hopelessness, feeling healthy, fear of being known to have HIV/AIDS status, stigma and discrimination, lack of support and motivation, bad roles from family and society, shame, work as a spiritual teacher, Confidence, poor economic conditions, and forgetting to take medication are factors that hinder adherence to PLWHA. Conclusion: The most common barrier to adherence of PLWHA in undergoing antiretroviral therapy is lack of knowledge and felt healthy that make PLWHA doesn’t need to take ARV therapy.